Catholics and their Scriptures: Six Ways of Engaging with the Bible - Ford, David G. (Ecclesial practices, 2019)
In recent years the Catholic Church has been encouraging its members to engage with the Bible and a variety of resources have been produced to facilitate this. However, national surveys in Britain show that Catholics are some of the Christians least likely to engage with the Bible outside of a church setting. A small focus group of ordinary Catholics spent a year using five different resources to ascertain what ways of engaging with the Scriptures they found most helpful. Six ways were identified: reading the Bible in community; drawing on secondary expertise; valuing the literal and spiritual sense of Scripture; focusing on the Old Testament and the Bible's unity; using accessible formats; and using a variety of resources. These are presented and discussed in the context of the Church's recent teaching and instruction on the role of the Bible in the life of the believer.